Total hemoglobin mass, iron status, and endurance capacity in elite field hockey players - Hinrichs, T.; Franke, J.; Voss, S.; Bloch, W.; Schanzer, W.; Platen, P. (The Journal of Strength and Conditioning Research, 2010)
The aims of this study were as follows: To evaluate total hemoglobin mass (tHbmass) in international field hockey players; to examine the correlation between tHbmass and maximum oxygen uptake (VO2max); and to assess influences of iron status on tHbmass and on VO2max. The players of the German women's (N = 17, aged 24.8 ± 3.0 [21-31] years) and men's (N = 17, aged 24.2 ± 2.9 [19-32] years) national field hockey team were investigated. tHbmass was measured by an optimized carbon monoxide rebreathing method. The following parameters were measured in venous blood: Hemoglobin concentration (Hbconc), hematocrit (Hct), number and percentage of reticulocytes, reticulocyte hemoglobin content, serum iron, serum ferritin, serum transferrin, unsaturated iron-binding capacity, and serum soluble transferrin receptor concentration. VO2max was determined in a treadmill test. tHbmass (women: 10.6 ± 1.1 g/kg; men: 12.5 ± 0.9 g/kg) correlated to VO2max (women: 46.6 ± 2.9 mL/min/kg; men: 55.8 ± 4.0 mL/min/kg) in women (r = 0.56, p < 0.05) and in men (r = 0.57, p < 0.05), whereas Hbconc and Hct did not. The investigated parameters of iron status showed no association to tHbmass or to VO2max. In conclusion, tHbmass can be used as an indicator for endurance capacity in elite field hockey players, whereas Hbconc may not. tHbmass or VO2max were not influenced by the actual iron status of the investigated athletes.